Iptek Bagi Masyrakat (IbM) Kelompok Usaha Peternak Ayam & Bebek - Idiar Idiar; Erwansyah Erwansyah; Sugianto Sugianto (Manutech : Jurnal Teknologi Manufaktur, 2017)
One of the efforts that became the target of development in the community by the Simpang Rimba district is chicken and duck farms. This is supported by the large availability of plants that will be used as animal feed such as cassava and taro stalk. However, currently the process of making animal feed is still done manually that is chopped by using a knife or a machete so that the time taken is long and the resulting capacity is limited. The purpose of science and technology for the community of chicken and duck breeders is to increase the production capacity of animal feed up to 100% and the uniformity of the cultivated product increases 100%. The method of implementation used in this service is to make a machine of cattle feed after doing a short training on the operation and maintenance of machinery to partners. Based on the results obtained the use of cassava chopper machine and taro stalk can increase the production process 40 kg within 30 minutes and the thickness of cassava size obtained an average of 2-7 mm so that the percentage of countable can be consumed 100% increase.